ED50 and ED95 of Propofol Combined with Different Doses of Intravenous Lidocaine for First-Trimester Uterine Aspiration: A Prospective Dose-Finding Study Using Up-and-Down Sequential Allocation Method - Zhang J; Kong L; Ni J (Dove Medical Press, 2022)
Jingwen Zhang,1 Linglingli Kong,2 Juan Ni1 1Department of Anesthesiology, West China Second University Hospital, Sichuan University, Key Laboratory of Birth Defects and Related Diseases of Women and Children, Sichuan University, Ministry of Education, Chengdu, Sichuan, People's Republic of China; 2Department of Obstetrics and Gynecology, West China Second University Hospital, Sichuan University, Key Laboratory of Birth Defects and Related Diseases of Women and Children, Sichuan University, Ministry of Education, Chengdu, Sichuan, People's Republic of ChinaCorrespondence: Juan Ni, Department of Anesthesiology, West China Second University Hospital, Sichuan University, Key Laboratory of Birth Defects and Related Diseases of Women and Children, Sichuan University, Ministry of Education, No. 20, Section 3, South of Renmin Road, Chengdu, Sichuan, 610041, People's Republic of China, Tel +86 18180609890, Fax +86 2885503752, Email nijuankiki@163.comPurpose: This study aimed to test the effect of different doses of intravenous lidocaine on the median effective dose (ED50) and 95% effective dose (ED95) of propofol-induction dose and identify the optimal dose.Patients and Methods: Patients undergoing first-trimester uterine aspiration were screened and randomly enrolled into the following groups: saline (L0), 0.5 mg/kg lidocaine (L0.5), 1.0 mg/kg lidocaine (L1.0), and 1.5 mg/kg lidocaine (L1.5). Anesthesia was induced with 1.0 μg/kg fentanyl. Prepared lidocaine or saline solution was injected later according to allocation, followed by propofol. The dose of propofol for each patient was determined using the up-and-down sequential study design. The primary end point was the ED50 and ED95 of the propofol-induction dose. The total propofol doses, awakening time, and adverse events were recorded.Results: The ED50 (95% confidence interval) of propofol was significantly lower in groups L1.0 and L1.5 than group L0 (1.6 [1.5- 1.7] mg/kg and 1.8 [1.6- 1.9] mg/kg, versus 2.4 [2.3- 2.5] mg/kg, respectively; p< 0.001). There was no significant difference in ED50 between groups L1.0 and L1.5 (p> 0.05). However, surprisingly, the ED50 was significantly higher in group L0.5 than L0 (2.8 [2.6- 3.0] mg/kg vs 2.4 [2.3- 2.5] mg/kg; p< 0.05). The total doses of propofol in groups L1.0 and L1.5 were lower than those in groups L0 and L0.5 (p< 0.05). The systolic blood pressure (SBP) decline after anesthesia induction in group L0.5 was greater than that in group L0 (p< 0.01). The incidence of respiratory depression in group L0.5 was greater than that in groups L0 and L1.0 (p< 0.05).Conclusion: In patients who underwent first-trimester uterine aspiration, intravenous lidocaine 1.0 mg/kg prior to propofol injection significantly reduced the ED50 of propofol induction dose without severe side effects, equivalent to the effect of 1.5 mg/kg dose. We recommend 1.0 mg/kg as the optimal dose.Keywords: lidocaine, propofol, uterine aspiration, median effective dose